A curriculum for the senior secondary years (Hawthorn, Vic. : Australian Council for Educational Research, 1992)
This book is about: Setting the scene; State of the art; Responding to the issues of post-compulsory schooling; Looking forward and an agenda.
Keywords: Education; Curriculum planning; Secondary education; Education, Secondary -- Australia -- Curricula; Curriculum planning -- Australia